Augmented survival of out-of-hospital cardiac arrest victims with the use of mobile phones for emergency communication under the DA-CPR protocol getting information from callers beside the victim. (October 2016) - Maeda, Tetsuo; Yamashita, Akira; Myojo, Yasuhiro; Wato, Yukihiro; Inaba, Hideo
Abstract: Purpose: To investigate the impacts of emergency calls made using mobile phones on the quality of dispatcher-assisted cardiopulmonary resuscitation (DA-CPR) and survival from out-of-hospital cardiac arrests (OHCAs) that were not witnessed by emergency medical service (EMS). Methods: In this prospective study, we collected data for 2530 DA-CPR-attempted medical emergency cases (517 using mobile phones and 2013 using landline phones) and 2980 non-EMS-witnessed OHCAs (600 using mobile phones and 2380 using landline phones). Time factors and quality of DA-CPR, backgrounds of callers and outcomes of OHCAs were compared between mobile and landline phone groups. Results: Emergency calls are much more frequently placed beside the arrest victim in mobile phone group (52.7% vs. 17.2%). The positive predictive value and acceptance rate of DA-CPR in mobile phone group (84.7% and 80.6%, respectively) were significantly higher than those in landline group (79.2% and 70.9%). The proportion of good-quality bystander CPR in mobile phone group was significantly higher than that in landline group (53.5% vs. 45.0%). When analysed for all non-EMS-witnessed OHCAs, rates of 1-month survival and 1-year neurologically favourable survival in mobile phone group (7.8% and 3.5%, respectively) were higher than those in landline phone group (4.6% and 1.9%; p  < 0.05). Multiple logistic regression analysis, including other backgrounds, revealed that mobile phone calls were associated with increased 1-month survival in the subgroup of OHCAs receiving bystander CPR (adjusted odds ratio, 1.84; 95% CI, 1.15–2.92). Conclusion: Emergency calls made using mobile phones are likely to augment the survival from OHCAs by improving DA-CPR.